GENDER AND PHYSICAL EDUCATION: WHAT IS "BOY"? WHAT IS "THE GIRL"? (Fiep Bulletin - online, 2016)
The present study addressed the issue of gender in physical education at school, had a general objective to present evidence to justify the choice of certain sports practices within the school environment, specifically regarding sports practices. A field survey was conducted through a questionnaire for graduates teachers in Physical Education working in state schools in the urban area of the Pirai South - Paraná. The results show that society is determining in sports practices of the students and also that most of the teachers separate students in separate classes related to sports, justifying that separation occurs for several reasons.
Keywords: Physical Education; Gender; sports practices.